An introduction to culture and psychology : a sociocultural perspective - Chirkov, Valery I. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The book offers an innovative introduction to culture and psychology, taking a sociocultural approach to understand the intricacies of culture-mind-behaviour interactions. In this book the author emphasises the dynamic relationship of the culture and the mind, outlining how organized sociocultural models regulate actions and practices across different domains of people's lives such as parenting, education, communication, and acculturation. Each chapter features chapter's synopsis, boxed examples, a glossary of key terms, reflective questions, and recommended reading to help students engage further with the material. The book includes a range of fascinating cross-cultural case study examples and discussions which offer insights into the intricate connections between culture, human psyche, and behaviour. An Introduction to Culture and Psychology is essential reading for undergraduate students taking culture and psychology courses. It can also be of interest to scholars of psychology, anthropology, sociology, communication, and other related disciplines"--
Keywords: Ethnopsychology; Culture -- Psychological aspects; Psychology -- Social aspects; PSYCHOLOGY / General; PSYCHOLOGY / Social Psychology